Substantial Heritability Underlies Fairness Norm Adaptation Capability and its Neural Basis - Yuening Jin; Dang Zheng; Ruolei Gu; Qingchen Fan; Martin Dietz; Changshuo Wang; Xinying Li; Jie Chen; Yuanyuan Hu; Yuan Zhou (Advanced Science, 2025)
Abstract The present research uncovers the shared genetic underpinnings of fairness norm adaptation capability, its neural correlates, and long‐term mental health outcomes. One hundred and eighty‐six twins are recruited and played as responders in the Ultimatum Game (UG) while undergoing fMRI scanning in their early adulthood (Study‐1) and are measured on depressive symptoms eight years later (Study‐2). With computational modeling, the process of norm adaptation is differentiated from that of fairness valuation in UG. The two processes both have moderate levels of heritability. The anterior insula has a significant phenotypic correlation, whereas the Supplementary Motor Area/Medial Frontal Gyrus (SMA/mSFG) shows both a significant phenotypic correlation and a shared genetic influence with the learning rate, an index for norm adaptation. The dopaminergic DRD2 polymorphisms correlate with both the learning rate and the SMA/mSFG encoding of prediction error, constituting of their common genetic basis. Regional gene expression analysis reveals the high expression of dopamine‐related genes in the SMA/mSFG. Moreover, the learning rate can predict depressive symptom severity eight years later, with the DRD2 polymorphisms constituting their shared genetic basis. This suggests that heritability is a non‐negligible driving force behind norm adaptation, which facilitates the learning of social norms in changing environments and preserves long‐term mental health.